Polycystic ovarian syndrome: an updated review of pathophysiology, clinical features, biomarkers, and management - Blessy S. Joseph; Dineshkumar B.; K. Krishna Kumar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2026)
Polycystic ovary syndrome (PCOS) is one of the most prevalent endocrine and metabolic disorders affecting women of reproductive age and represents a major global public health challenge. PCOS is a heterogeneous condition characterized by reproductive dysfunction, hyperandrogenism, insulin resistance (IR), and metabolic abnormalities, frequently accompanied by psychological distress that significantly reduces quality of life. Despite its high prevalence, diagnosis, treatment, and long-term management remain challenging due to its complex, multifactorial pathophysiology. This review provides a comprehensive overview of the epidemiology, diagnostic criteria, clinical manifestations, and etiological factors associated with PCOS, with particular emphasis on genetic susceptibility, epigenetic regulation, environmental exposures, dietary habits, and lifestyle factors contributing to disease onset and progression. Key pathophysiological mechanisms are explored, including IR, hyperandrogenism, follicular arrest, chronic low-grade inflammation, oxidative stress, mitochondrial dysfunction, and adipose tissue dysregulation. The clinical manifestations of PCOS reproductive, metabolic, hyperandrogenic, and psychological along with long-term complications such as type 2 diabetes mellitus (T2DM), cardiovascular disease (CVD), non-alcoholic fatty liver disease (NAFLD), endometrial disorders, infertility, and adverse pregnancy outcomes, are discussed. Emerging hormonal, inflammatory, metabolic, genetic, and molecular biomarkers are highlighted for their potential to improve diagnosis, phenotypic classification, and personalized therapy. Current treatments, including lifestyle modification, pharmacological interventions, nutritional supplementation, and emerging targeted therapies, are also summarized. A deeper understanding of the molecular mechanisms underlying PCOS is essential for enabling early diagnosis, optimizing individualized management, reducing long-term health risks, and improving outcomes through precision medicine, multidisciplinary care, evidence-based decision-making, and continued therapeutic innovation.